Roman J. Israel, Esq. [videorecording (DVD)] - Washington, Denzel, 1954-; Gilroy, Dan, 1959-; Farrell, Colin, 1976-; Ejogo, Carmen, 1974- (Sony Pictures Home Entertainment, 2018)
Denzel Washington stars as Roman Israel, a driven, idealistic defense attorney who, through a tumultuous series of events, finds himself in a crisis that leads to extreme action.